2020
DOI: 10.1007/s40496-020-00282-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress: A Predisposing and Exacerbating Factor in Periodontitis

Abstract: Purpose of Review This review focuses on recent advances in our understanding of the interactions between psychological stress, the immune system, and periodontitis, including the dynamic role of host stress responses in altering immune function, altering the oral microbiome and biofilm formation, and promoting local and systemic disease progression. Recent Findings Within the context of periodontal health and disease, stress leads to an impairment of effective antimicrobial defense, shifts in oral microbiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 90 publications
(107 reference statements)
3
18
0
Order By: Relevance
“…Emerging evidence suggests that chronic stress and related diseases, such as depression and anxiety, may be significant factors contributing to the development of oral dysbiosis, progression of periodontal/ peri-implant disease, and inconsistent wound healing following periodontal therapy. 125,[224][225][226] Moreover, the stress hormone, cortisol, has been shown to directly induce shifts in the composition of the oral microbial community and in its gene expression profiles in vitro, which reproduces results found for the gene expression profiles of the oral microbial community in periodontal disease and during its progression. 94…”
Section: Oral Microbiome In Systemic Diseasesupporting
confidence: 76%
“…Emerging evidence suggests that chronic stress and related diseases, such as depression and anxiety, may be significant factors contributing to the development of oral dysbiosis, progression of periodontal/ peri-implant disease, and inconsistent wound healing following periodontal therapy. 125,[224][225][226] Moreover, the stress hormone, cortisol, has been shown to directly induce shifts in the composition of the oral microbial community and in its gene expression profiles in vitro, which reproduces results found for the gene expression profiles of the oral microbial community in periodontal disease and during its progression. 94…”
Section: Oral Microbiome In Systemic Diseasesupporting
confidence: 76%
“…Several recent systematic reviews of the current literature have pointed to an increasing platform linking chronic psychosocial stress/disorders with diseases of the periodontium/periosteum [1][2][3] attributable to dynamics in the immune system, oral microbiome shifts/biofilm formation, enzymatic-mediated protein/collagen turnover ratios, and local/systemic disease progression. 4 Towards this end, there are three possible interactions between the periodontium/periosteum and stress: stress → periodontium/periosteum, periodontium/periosteum ← stress, and stress ↔ periodontium/periosteum. 5 These three interactions will be explored throughout this paper to assess the psychobiologic links between chronic stress-related diseases and periodontal/peri-implant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that a complex biological indicator to be established in a series of studies will allow treatment tailored to risk level, which may be beneficial for future personalized periodontics. In addition, Spector et al showed that stress affects periodontal disease by enhancing bacteriological factors through impaired antimicrobial defense, more pathogenic gene expression, and shifts in the oral microbiome profile with taxa composition [ 152 ].…”
Section: Next-generation Procedures In Periodontal Diseasementioning
confidence: 99%